2011
DOI: 10.1007/s00424-011-1059-6
|View full text |Cite
|
Sign up to set email alerts
|

NHE1 activity contributes to migration and is necessary for proliferation of human gastric myofibroblasts

Abstract: Myofibroblasts play central roles in wound healing, deposition of the extracellular matrix and epithelial function. Their functions depend on migration and proliferation within the subepithelial matrix, which results in accelerated cellular metabolism. Upregulated metabolic pathways generate protons which need to be excreted to maintain intracellular pH (pH(i)). We isolated human gastric myofibroblasts (HGMs) from surgical specimens of five patients. Then we characterized, for the first time, the expression an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 64 publications
0
31
0
1
Order By: Relevance
“…The details of patients can be found in Table 1. The isolation of myofibroblasts was performed using a previously described method (6). Briefly, the specimens were washed and chopped into ϳ1-to 2-mm 3 pieces and were then bathed in a shaking water bath at 37°C for 15 min with 1 mM dithiothreitol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The details of patients can be found in Table 1. The isolation of myofibroblasts was performed using a previously described method (6). Briefly, the specimens were washed and chopped into ϳ1-to 2-mm 3 pieces and were then bathed in a shaking water bath at 37°C for 15 min with 1 mM dithiothreitol.…”
Section: Methodsmentioning
confidence: 99%
“…After gentle washing for three times with serum-free media, an inverted light microscope was used to measure and photograph wounds. Reagents were then added to the wells in serum-free media, and HGMs were incubated in a CO 2 incubator at 37°C for 24 h. Migration was evaluated by counting the cells in the same area of the wound after 24 h as reported earlier (6). Proliferation assay.…”
Section: G554mentioning
confidence: 99%
See 1 more Smart Citation
“…(75,86,87) Using NHE isoform specific inhibitor HOE-642, we determined that NHE-1 and NHE-2 are participating in the restoration of pHi which is rather attributable to NHE-1. This finding was in accordance with Goldman et al who found that 60% of pHi recovery is mediated through NHE-1.…”
Section: Discussionmentioning
confidence: 99%
“…NBC represents another important pHi regulatory mechanism in several types of epithelial cells (75)(76)(77). In the case of EECs, in standard HCO3 -/CO2-buffered extracellular solution, the pHi of CP-A cells rapidly decreased by the quick diffusion of CO2 into the cytoplasm.…”
Section: Amentioning
confidence: 99%